The effect of Rofecoxib on the degree and rate of orthodontic tooth movement in guinea pigs - Paulino, Even Grace M.
Researches indicate that pain associated with orthodontic treatment ranks as the most discouraging factor related to the treatment as well as the highest-ranking reason for patients to want to discontinue orthodontic care. The most common medications used in the orthodontic arena are presumably and non-steroidal anti-inflammatory drugs (NSAIDs). They function by inhibition of the cyclooxygenase (COX) enzyme system which results in the suppression of the biosynthesis of prostaglandins. Blocking the synthesis of prostaglandins however, has resulted in slower tooth movement. The purpose of the present study is to examine the influence of rofecoxib, a NSAID specific COX-2 inhibitor, on the degree and rate of orthodontic tooth movement in guinea pigs. Twenty-four guinea pigs were chosen for the study, twelve of which received 50 mg of rofecoxib administered orally for the first five days of the 16-day observation period while the other twelve animals served as controls. Titanium molybdenum alloy helical torsion springs delivering 25 grams of force were engaged on a stainless steel band with welded edgewise bracket with single wing on the maxillary central incisors. Direct linear measurements of tooth separation were recorded at days 2, 3, 4, 5, 6, 11 and 16. Histological examinations on the sixth day showed a significant decrease in the number of Howship's lacunae and osteoclasts in the rofecoxib group. However, rofecoxib did not appear to significantly affect orthodontic tooth movement (P > 0.05). Findings of this study imply that the limited time that rofecoxib is present in the serum level is insufficient to cause significant reduction of prostaglandin thus, is also insufficient to inhibit tooth movement. The results suggest that rofecoxib can be used during orthodontic treatment without inhibitory effect on the degree and rate of orthodontic tooth movement, but further clinical study is recommended.